2021
DOI: 10.3389/fcell.2021.685913
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii Type-I ROP18 Targeting Human E3 Ligase TRIM21 for Immune Escape

Abstract: Toxoplasma gondii is an intracellular pathogen that exerts its virulence through inhibiting host’s innate immune responses, which is mainly related to the type II interferon (IFN-γ) response. IFN-γ inducible tripartite motif 21 (TRIM21), an E3 ligase, plays an important role in anti-infection responses against the intracellular pathogens including bacteria, virus, and parasite. We found that T. gondii virulence factor ROP18 of the type I RH strain (TgROP18I) interacted with human TRIM21, and promoted the latte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…The immune changes that occur after infection may have a role in determining the fetus gender or stimulating and protecting specific gender, thus increasing SSR. Immunosuppressive is one of the phenomenons in toxoplasmosis infection, Where the infection decreases NK cells, white cells and monocytes [34,35], which gives the greatest opportunity for male fetuses to develop, especially since they have the Y production on their surface. It was found that the male fetus is 1.62 times more than the female fetus is developing in the womb [31].…”
Section: Discussionmentioning
confidence: 99%
“…The immune changes that occur after infection may have a role in determining the fetus gender or stimulating and protecting specific gender, thus increasing SSR. Immunosuppressive is one of the phenomenons in toxoplasmosis infection, Where the infection decreases NK cells, white cells and monocytes [34,35], which gives the greatest opportunity for male fetuses to develop, especially since they have the Y production on their surface. It was found that the male fetus is 1.62 times more than the female fetus is developing in the womb [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, PV ubiquitylation is only moderately reduced in Trim21-deficient mouse cells, and the defect is limited to polyubiquitin chains linked at lysine residue 63 (K63) ( 38 ). TRIM21 also facilitates PV ubiquitylation in human fibroblasts infected with an avirulent type III strain of Toxoplasma but not in cells infected with a virulent type II strain that expresses high levels of the secreted virulence factor ROP18, a kinase targeting TRIM21 for lysosomal degradation ( 39 41 ).…”
Section: Introductionmentioning
confidence: 99%
“…In mouse embryonic fibroblasts (MEFs) and bone marrow-derived macrophages (BMDMs), TRAF6-mediated ubiquitination of type II and III vacuoles enhances the recruitment of GBPs, resulting in rupture of the PVM (Haldar et al ., 2015; Mukhopadhyay et al ., 2020). The E3 ligase TRIM21 has also been shown to promote clearance of type II and III strains in vivo (Foltz et al ., 2017), and ubiquitinates type III vacuoles in human foreskin fibroblasts (HFFs) resulting in parasite growth restriction (Yao et al ., 2021). In human umbilical vein endothelial cells (HUVECs), K63-linked ubiquitination initiates a cascade of autophagy marker recruitment that culminates in acidification of the parasite vacuole (Clough et al ., 2016), while in HeLa cells ubiquitination instead leads to recruitment of LC3 and stunting of parasite growth (Selleck et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%